The Global Epidemic of the SARS-CoV-2 Delta Variant, Key Spike Mutations and Immune Escape - Tian, Dandan; Sun, Yanhong; Zhou, Jianming; Ye, Qing (Frontiers in Immunology, 2021)
During the COVID-19 pandemic, SARS-CoV-2 variants have emerged and spread worldwide. The Delta (B.1.617.2) variant was first reported in India in October 2020 and was classified as a "variant of concern (VOC)" by the WHO on 11 May, 2021. Compared to the wild-type strain, several studies have shown that the Delta variant is more transmissible and has higher viral loads in infected samples. COVID-19 patients infected with the Delta variant have a higher risk of hospitalization, intensive care unit (ICU) admission, and mortality. The Delta variant is becoming the dominant strain in many countries around the world. This review summarizes and analyses the biological characteristics of key amino acid mutations, the epidemic characteristics, and the immune escape of the Delta variant. We hope to provide scientific reference for the monitoring and prevention measures of the SARS-CoV-2 Delta variant and the development strategy of a second-generation vaccine.